SportAccord (2014)
SportAccord (previously known as GAISF, the General Association of International Sports Federations) is a not-for-profit association, composed of autonomous and independent international sports federations and other international organisations contributing to sport in various fields. SportAccord is constituted according to article 60ff of the Swiss Civil Code, is governed by Swiss law and is formed for an unlimited period of time. The registered office of SportAccord is located in Lausanne, Switzerland. SportAccord is the UNION for both Olympic and non-Olympic international sports federations as well as organisers of international sporting events. SportAccord`s mission is to UNITE and SUPPORT its members in the co-ordination and protection of their common aims and interests, while preserving and respecting their autonomy. SportAccord encourages and facilitates knowledge sharing among members and provide resources and expertise in relevant areas such as anti-doping, integrity, good governance, social responsibility and digital media. By establishing several premier multi-sports games that group together similar sports, SportAccord aims to promote its members and increases their visibility and resources. As an organisation, SportAccord identifies with the key values of neutrality, transparency and accountability while promoting sport`s ability to contribute to positive change in society.